Immunohistochemical Estimates of Angiogenesis, Proliferative Activity, p53 Expression, and Multiple Drug Resistance Have No Prognostic Impact in Osteosarcoma: A Comparative Clinicopathological Investigation. (31st December 2008) - Sorensen, Flemming Brandt; Jensen, Kenneth; Vaeth, Michael; Hager, Henrik; Funder, Anette Mariane Daa; Safwat, Akmal; Keller, Johnny; Christensen, Mariann
Abstract : Purpose . To investigate angiogenesis, multiple drug resistance (MDR) and proliferative activity as prognostic variables in patients suffering from osteosarcoma. Methods . Histologic biopsies from 117 patients treated in the period from 1972 through 1999 were immunohistologically investigated regarding angiogenesis (CD34), proliferative activity (MIB-1), and the expression of p53 and MDR (P-glycoprotein (Pgp); clones JSB-1, C494, and MRK16). Quantitative and semiquantitative scores of immunoreactive cells were analyzed statistically along with retrospectively obtained clinicopathologic variables. Results . Chemotherapy reduced the rate of amputations (P = .00002 ). The Pgp was overexpressed (score ≥2) in 48% of the primary, diagnostic biopsies, and high Pgp correlated with high Pgp in postsurgical specimens (P = .003 ). In contrast, no such associations were disclosed for estimates of angiogenesis (P = .64 ) and p53 (P > .32 ), whereas the MIB-1 index was reduced in the post-chemotherapy specimens (P = .02 ). The overall, disease-specific survival was 47%, increasing to 54% in patients receiving pre-operative chemotherapy. Statistical analyses showed prognostic impact exclusively by patient age and type of osteosarcoma. Discussion . The studied series of patients documented already prior to the chemotherapy era, a rather excellent survival and estimates of angiogenesis, proliferation, p53, and Pgp expressions, did not demonstrate sufficient power to serve as predictors of treatment response or survival.